Fortifying home IoT security: A framework for comprehensive examination of vulnerabilities and intrusion detection strategies for smart cities - Akashdeep Bhardwaj; Salil Bharany; Anas W. Abulfaraj; Ashraf Osman Ibrahim Elsayed; Wamda Nagmeldin (Elsevier B.V., 2024)
Smart home devices have brought in a disruptive, revolutionary Internet-based ecosystem that enhanced our daily lives but has pushed private data from inside our homes to external public sources. Threats and attacks mounted against IoT deployments have only increased in recent times. There have been several proposals to secure home automation environments, but there is no full protection against Cybersecurity threats for our home IoT platforms. This research investigates attack attempts on smart home environments, focusing on firmware, brute force, and DoS attacks on the Internet of Things (IoT) network which were successful in bringing down the device in less than a minute. Weak passwords were cracked using Brute Force techniques related to HTTP, SSH, Telnet, and FTP protocols, and an unknown service port to reveal backdoor access. Cross-site scripting vulnerability was detected on IoT devices that could allow running malicious scripts on the devices. The authors also exploited the unknown services to reveal backdoors and access sensitive device details and potentially exploited them to add new ports or rules to turn the IoT devices into a router to attack other devices. To detect and mitigate such attacks, the authors present an IoT-based intrusion detection and prevention system to secure smart home network devices. The authors compared the proposed framework with other similar research based on Precision, Accuracy, F-measure, and Recall. The proposed model outperforms all the other known models reporting a high of 95% for identifying malicious attack packets, while others reported 58% and 71% detection percentage.